2018
DOI: 10.4067/s0717-75262018000200186
|View full text |Cite
|
Sign up to set email alerts
|

Atelectasia maxilar crónica bilateral con resolución espontánea

Abstract: RESUMEN La atelectasia maxilar crónica (AMC) es una condición adquirida y rara

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…If septal deviation, septoplasty can be performed in the same act, as demonstrated by Darghal et al in four of the eleven patients presented [11], and as was done in our patient in Case 2. Intraoperatively, much attention is needed when there is a lateralisation of the uncinate process when there is hypoglobus, as its incorrect identification can lead to eye damage [7]. Fortunately, none of the reported patients had ocular complications, only one of them had mild epistaxis and synechia, that were resolved.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…If septal deviation, septoplasty can be performed in the same act, as demonstrated by Darghal et al in four of the eleven patients presented [11], and as was done in our patient in Case 2. Intraoperatively, much attention is needed when there is a lateralisation of the uncinate process when there is hypoglobus, as its incorrect identification can lead to eye damage [7]. Fortunately, none of the reported patients had ocular complications, only one of them had mild epistaxis and synechia, that were resolved.…”
Section: Discussionmentioning
confidence: 95%
“…Considering this, we can classify our patients here described as having CMA (cases 1 and 2 as stage II and case 3 as stage III), since two of them had significant complaints of facial pain and one of hyposmia. Therefore, it is clear that sinonasal symptoms have a fundamental role in this differentiation, which even justifies the "silent" course of SSS [7]. However, it is observed that at least one-half of the cases described as CMA or SSS have a similar history of mild rhinosinusitis, showing a lack of padronization in the literature [1].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation